Small-aperture corneal inlay in presbyopic patients with prior phakic intraocular lens implantation surgery: 3-month results - Huseynova, Tukezban (Dove Medical Press, 2013)
We report a series of three case reports of KAMRA inlay implantation procedures in presbyopic patients with a history of prior phakic intraocular lens implantation surgery. Three-month results showed a two to five-line improvement for uncorrected near visual acuity. The absolute uncorrected near visual acuity change for case 1 was from J4 to J2, for case 2 was from J6 to J4, and for case 3 was from J10 to J5. No significant change of uncorrected distance visual acuity was observed in all three cases.